Sulfur dioxide (SO2) levels in the air of the city of Tingo María comparing two modified methods - Inga Fernández, Fresia (2022)
The objective of this research was to evaluate two modified methods to determine sulfur dioxide (SO2). The sampling was carried out in five representative zones of the city of Tingo Maria through the sampling train and Palmes tubes, the analyses were carried out in the environments of the Laboratory of the Biotechnological Research Center of the Amazon at the National Agrarian University of the Jungle, in the District of Rupa Rupa, Department of Huanuco. The results indicate that the method proved to be linear (r2 = 0.996), accurate (CV < 11 %), sensitive (LOD = 0.028 ug or 0.933 ug/m3 and LC = 0.93 ug or 3.100 ug/m3) and robust (P-value > 0.05). According to the results of the method performance, the proposal of method FIF-19029417 was elaborated to determine SO2 by visible spectrophotometry according to NTP - ISO/IEC 1725 (2006). In the determination of SO2 it was observed that, during the evaluation, SO2 levels are well below the limit established by the RCTs and the WHO guide, finally the concentrations obtained using the passive sampler versus the active sampler, provided excellent correlations between both sampling methods (r2 ≥ 0.90).